REVENUE FARMING AND IMPERIAL TRANSITION: AN ECONOMIC DIMENSION OF EARLY COLONIAL STATE FORMATION IN JAVA, C. 1800s-1820s - Abdul Wahid (Humaniora, 2012)
Revenue farming (pacht or verpachtingen in Dutch) is a fiscal institution that existed in Java since the pre-colonial period. During the VOC period, the Dutch modified, institutionalized and &extended it as one of their fiscal institutions to solve human resource shortage and administrative barriers in collecting taxes from local population. For political and economic reasons the Dutch favored the Chinese as main partners in operating the system. The system was proven efficient to an extent that it collected substantial revenue contribution to the state exchequer. During the period of 'imperial'  transition from 1800s until 1820s, changing regimes in Java retained the system to finance their political agenda. This paper argues that revenue-farming system was the financial source for the Dutch in establishing a real colonial state in Java.